Thomas Kuhn, Hyperbole, and the Ashtray: Evidence of Morris' Faulty Memory. Issue 1 (22nd January 2023) - Wray, K. Brad
Abstract: Errol Morris has claimed that Kuhn threw an ashtray at him during a dispute about some matter in the history of science. Morris also claims that Kuhn threw him out of the graduate program at Princeton for disagreeing with him. I argue that Morris's attack on Kuhn contains some degree of hyperbole. Further, I present evidence that shows that Morris is mistaken about key events during this period. In fact, Kuhn was supportive of Morris in his pursuit of a career in the history of science.